Análise da segurança do paciente com doença renal crônica em clínicas de hemodiálise - Lima, Magda Milleyde de Sousa (2021)
Patients with chronic kidney disease are vulnerable to episodes that put their health's safety at risk, mainly due to the treatment process that exposes them to high rates of interventions. Some factors associated with health care contribute to the risk of complications and death, of which the following stand out: administration of potentially dangerous drugs, continuous use of vascular access and interdisciplinary work. Thus, the objective was to analyze the safety of patients with chronic kidney disease in hemodialysis clinics. An observational, analytical and cross-sectional study was carried out. The study sample consisted of 200 chronic kidney patients, 30 nursing technicians and seven nurses from three payment hemodialysis clinics in Fortaleza-CE. The inclusion criteria for patients were: being present at the hemodialysis session on the day of data collection and being 18 years of age or older. In turn, nurses and nursing technicians who assisted the patients included in the study were selected. Data collection occurred from September to November 2019 through the application of the sociodemographic and clinical characterization form and the Chronic Renal Patient Safety Assessment Scale in Hemodialysis. The data were formed by descriptive and analytical statistics using the SPSS version 20.0 statistical package. The present study respected the ethical and legal principles under the approval of the Ethics and Research Committee of the Federal University of Ceara with opinion 3,255,635. The results found showed statistical significance in the level of safety between the three hemodialysis clinics (p = 0.000). Clinics 1 and 2 safe care practices and clinic 3 unsafe care practices, with averages of 37.3, 37.7 and 32.2 points, respectively. The difference in statistics was identified between the level of safety with the sociodemographic and clinical variables of patients using medication (p = 0.008) and correlation with time on hemodialysis (p = 0.002; rô = 0.216). When assessing the profile of health professionals, statistical differences were evidenced between the level of security with sociodemographic variables: marital status [nurse (p = 0.000)], race [nurse (p = 0.017) and nursing technician (p = 0.025) )], degree of education [nurse (p = 0.000)], income [nurses (p = 0.013) and nursing technician (p = 0.000)], religion [nursing technician (p = 0.008)] and correlation with variables: age [nurse (p = 0.000; rô = 0.390)], weekly workload at the institution [nurse (p = 0.000 and rô = 0.359)]; nursing technician (p = 0.010; rô = 0.183)], time working with hemodialysis [nurse (p = 0.000; rô = 0.529)], time working at the institution [nurse (p = 0.007; rô = 0.193)] and dimensioning of the institution [nurse (p = 0.000; rô = 0.334)]. Thus, it is concluded that there is non-conformity in a studied clinic and that sociodemographic and clinical factors of patients and health professionals corroborate the 14 level of safety. Thus, it is necessary to implement training processes within the scope of health education and to develop new guidelines for patient safety in the clinic with non-compliance.